Energy expenditure estimated by accelerometry and doubly labeled water: Do they agree? - Leenders, N. Y.; Sherman, W. M.; Nagaraja, H. N. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The purpose of this study was to compare energy expenditure derived from regression equations determined from accelerometry with energy expenditure obtained from the doubly labeled water method (DLW).